Constitution, Fundamental Law, of the Union of Soviet Socialist Republics : As Enmended and Added to at the Third Session of the Supreme Soviet of the USSR Fifth Convocation (1960)
Texto de la constitución rusa aprobada el 5 de diciembre de 1936 con que se reformó el gobierno de la Unión Soviética bajo el mandato de Stalin. Estuvo vigente hasta 1977.